Analysis of the breaking process and the components of the crown structure after a single droplet hits thin liquid film. (25th January 2023) - Lu, Lili; Pei, Yiqiang; Qin, Jing; Peng, Zhijun; Zhong, Kai
Highlights: Three types of crown breakup: splash breaking, hole breaking, and mixed breaking. Fluid film viscosity and droplet Weber number affect the crown breakup. Empirical correlations to classify-three types of crown breakup was proposed. Abstract: The breaking process and the components of the crown formed when the single droplet impact on different liquid films were investigated experimentally and simulatly. Laser-induced fluorescence (LIF) methods were used to study the breakup process of the crown structure. The composition of the incident droplets in this test is ethanol, and the glycerol aqueous solution was used as the liquid film. Results show that at different droplet Weber numbers, liquid film thickness, and liquid film viscosity, it is reasonable to classify the breakup of crown structure into the following three regimes: splash breaking, hole breaking, and mixed breaking. The characteristics of each breaking regime, such as the breaking mechanism, diameter of crown structure and spatial distribution of the secondary droplets formed after breakup, have been qualitatively analyzed. The viscosity of the liquid film and the Weber number of incident droplets have significant influence on the breakup of the crown structure. With decreasing viscosity and increasing Weber number, the crown structure breaking process transits from unbroken to splash breaking, hole breaking, and finally mixed breaking. According to the experimental results, a fitting formula for describing critical parameters of the different breaking regimes of crown structure is established. To further quantify the material components of the crown structure and the mixing of the incident droplets with the liquid film, Volume of Fluid (VOF) model and species transport model were used to establish a model for simulation calculations, and the effects of droplet Weber number, liquid film thickness and liquid film viscosity were clarified.